An unusual new leafhopper species of Daochia Wei, Zhang & Webb, 2006(Hemiptera: Cicadellidae: Deltocephalinae: Stegelytrini) described from China - Fang, Yongqin; Webb, Mick; Xing, Jichun (Zootaxa, 2020)
A new leafhopper species Daochia fenestrata sp. nov. (Hemiptera: Cicadellidae: Deltocephalinae: Stegelytrini) from China is described with habitus photos and illustrations of male and female genitalia provided. In addition to its large and spectacular appearance the new species is unusual in having a transparent ‘window-like’ patch on the forewing. Another large, spectacularly marked species, Honguchia superba Wei & Webb, 2010, from Sumatra (Indonesia) is transferred to Daochia as D. superba comb. nov.. A checklist and key to Chinese genera of Stegelytrini are provided.